At school … with and without a computer: The importance of ICT in the school of the future - Dias, R.; Oliveira, A.; Cruz, M. (Applied Sciences, 2025)
We live in a globalised, knowledge-hungry society in which the immediacy of information is increasingly a necessity that has become a reality even in the most remote places. This article aims to reflect on the importance of Information and Communication Technologies (ICT) in education, emphasising the need for skills and literacies in a globalised society. The school must provide tools that enable the acquisition of these competences, but the lack of continuous teacher training and adequate resources limits the effective use of these technologies in the classroom. The main research question concerns teachers’ perceptions of ICT, the most widely adopted technologies, and their impact on their daily lives. To answer the research question, we defined the main objectives as understanding teachers’ perceptions of ICT and identifying the technologies most used in teaching, highlighting how they can transform the learning process and improve the results of students, especially those with the most difficulties. The aim of this work is to find out how teachers perceive the use of ICT and, at the same time, to demonstrate that its use in the classroom enhances the teaching–learning process, making it more relevant, effective, and in line with the demands of the contemporary world.